Oxidized regenerated cellulose for a clear thoracoscopic view: a single-centre randomized trial. (20th November 2019) - Shimizu, Nahoko; Tanaka, Yugo; Kuroda, Sanae; Nakamura, Hayate; Matsumoto, Gaku; Mitsui, Suguru; Sakai, Shuto; Minami, Kazuhiro; Doi, Takefumi; Hokka, Daisuke; Maniwa, Yoshimasa
Abstract: : OBJECTIVES: During video-assisted thoracoscopic surgery (VATS), blood oozing from the surface of the access port wound can hamper the surgical view. Although this oozing is difficult to prevent, it can be decreased by placing a wound edge protector with oxidized regenerated cellulose (ORC) on the surface of the access port wound, thereby improving the surgical outcomes and safety of VATS. METHODS: We conducted a prospective, single-centre, open-label, randomized clinical trial to evaluate the operative outcomes of VATS when using the ORC (ORC group) compared with operative outcomes without using the ORC (non-ORC group). The primary end point was interruption of the operation as a result of blood oozing from the surface of the access port wound. The secondary end points were the other intraoperative and postoperative outcomes. RESULTS: A total of 108 patients were divided into the ORC group ( n  = 54) and the non-ORC group ( n  = 54). Compared with the non-ORC group, the ORC group had fewer patients with an interruption in the operation (11.1% vs 51.8%; P  < 0.001), less need for wound haemostasis of the access ports during wound closure (44.4% vs 72.2%; P  = 0.003), similar rates of postoperative deaths and complications and a tendency for shorter operation times (149.3 vs 168.8 min, respectively; P  = 0.083). CONCLUSION: The use of an ORC sheet around a wound edge protector for haemostasis can ensure a clear view during VATS. Clinical trial registration number: UMIN000031112.